Dielectrophoretic investigation of Bi2Te3 nanowires - A microfabricated thermoelectric characterization platform for measuring the thermoelectric and structural properties of single nanowires - Wang, Zhi; Kojda, Danny; Peranio, Nicola; Kroener, Michael; Mitdank, Ruediger; Toellner, William; Nielsch, Kornelius; Fischer, Saskia F.; Gutsch, Sebastian; Zacharias, Margit; Eibl, Oliver; Woias, Peter (Nanotechnology, 2015)
In this article a microfabricated thermoelectric nanowire characterization platform to investigate the thermoelectric and structural properties of single nanowires is presented. By means of dielectrophoresis (DEP), a method to manipulate and orient nanowires in a controlled way to assemble them onto our measurement platform is introduced. The thermoelectric platform fabricated with optimally designed DEP electrodes results in a yield of nanowire assembly of approximately 90% under an applied peak-to-peak ac signal Vpp=10 V and frequency f=20 MHz within a series of 200 experiments. Ohmic contacts between the aligned single nanowire and the electrodes on the platform are established by electron beam-induced deposition. The Seebeck coefficient and electrical conductivity of electrochemically synthesized Bi2Te3 nanowires are measured to be -51 μV K-1 and (943160)/(Ω-1 cm-1), respectively. Chemical composition and crystallographic structure are obtained using transmission electron microscopy. The selected nanowire is observed to be single crystalline over its entire length and no grain boundaries are detected. At the surface of the nanowire, 66.11.1 at.% Te and 34.91.1 at.% Bi are observed. In contrast, chemical composition of 64.2 at.% Te and 35.8 at.% Bi is detected in the thick center of the nanowire.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Bi; dielectrophoresis; structural analysis; thermoelectric platform; thermoelectric properties